Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Cookies Buah Gayam Di Dusun Panjangan - Azzahra, Atikah; Rahmawati, Amin Yoga; Tariani, Fitri; Nabilah, Khairina Putri; Hurek, Sriwahyuni Putri; Sukaca, Firola; Kurniasari, Yulinda (Universitas Alma Ata, 2023)
So many Gayam that we can find in Panjangan village, Sendangsari can be used as one of those things that can be used as food and also can be the resources to boost the economy at Panjangan Village. Gayam with the Latin name Inocarpus Fagifer contains antioxidants. At Panjangan Village, people boil Gayam and make chips from gayam. Therefore, doing development innovation in gayam processing which can increase market value and can also be consumed by all. The method used is observation and interviews at Panjangan Village, Sendangsari, Bantul. from developed innovation in gayam processing, produced a product namely Cookies gayam. Keywords: product development, cookies, gayam